The association between cognitive impairment and 30-day mortality among older Chinese inpatients - Zhang, Xiao-Ming; Jiao, Jing; Guo, Na; Zhu, Chen; Li, Zhen; Lv, Dongmei; Wang, Hui; Jin, Jingfen; Wen, Xianxiu; Zhao, Shengxiu; Wu, Xinjuan; Xu, Tao (Frontiers in Medicine, 2022)
Abstract Purpose: Although the association between cognitive impairment and mortality has been widely described among community-dwelling older adults, this association in hospitalized patients was limited. Objectives: This study’s purpose was to explore the association between cognitive impairment and 30-day mortality after adjustment of factors among Chinese in-patients. Methods: This was a large-scale prospective study based on a cohort of patients aged 65 years and older, whose cognitive function was assessed using the Mini-Cog instrument, followed up at 30-days for mortality. Multivariate logistic regression models were used to assess the association between cognitive impairment and 30-day mortality. Results: There were 9,194 inpatients in our study, with an average age of 72.41±5.72. The prevalence of cognitive impairment using the Mini-Cog instrument was 20.5%. Multivariable analyses showed that patients with cognitive impairment have an increased risk of 30-day mortality, compared to those with normal cognitive function (OR=2.83,95%CI:1.89-4.24) in an unadjusted model. In the fully adjusted model, Patients with cognitive impairment had an increased risk of 30-day mortality compared to those with normal cognitive function in the completely adjusted model (OR =1.76 ,95% CI: 1.14-2.73). Additionally, this association still existed and was robust after performing a stratified analysis of age, gender, frailty and depression, with no significant interaction (P>0.05). Conclusions: Our study found that older Chinese in-patients with cognitive impairment have a 1.76-fold risk of 30-day mortality compared to patients with normal cognitive function, suggesting that clinicians and nurses need to early implement cognitive function screening and corresponding interventions to improve clinical outcomes for older in-patients. Keywords: cognitive impairment, mortality, inpatients, older adults